The Introduction of the Austrian Toll System for Trucks - Effects on Companies - Einbock, Marcus (Communications - Scientific letters of the University of Zilina, 2006)
This paper deals with effects of the Austrian road pricing system on enterprises. Trucks are charged per kilometre driving on Austrian motorways with the amount depending on the number of axles. Therefore, enterprises whose trucks use motorways are confronted with higher transport costs. These costs can be generally divided into direct and indirect ones. The main cost categories concerning indirect costs are costs for pre-financing, for bad debts losses and for toll-control. In this contribution these kinds of costs are assessed and the cost effects in different industries are evaluated. Further, empirical evidence based on a survey conducted in June 2005 is included, where Austrian enterprises were asked about their assessments concerning consequences of road pricing on their company.